Internalization of Religious Moderation in Independent Curriculum Development - Putri, Mega Sulistiyani; Yahiji, Kasim; Ondeng, Syarifuddin; Arif, Muh. (Newinera Publisher, 2023)
This research raises three issues: How to internalize religious moderation in developing an independent curriculum in madrasas, what is the meaning of religious moderation, how to develop an independent curriculum in madrasas. The type of research used is qualitative research using observation, observation and documetation methods. The sources of research data include primary data and secondary data. Data collection techniques used by data reduction, data presentation, and verification. The results of this study show that, religious moderation is a conscious effort in understanding, instilling and cultivating an understanding of religious, ethnic, racial and cultural diversity through various approaches, strategies and appropriate methods so that moderate attitudes and behaviors are reflected in the values of religious moderation, among others, respect for diversity, tolerance, moderation, balance, and justice in each student. The curriculum was developed with the aim of improving the quality of education because the heart of an education is the curriculum.